Enhanced Dielectric Response in PVDF-HFP-GO-Ta2O5 Nanocom- posites: Synthesis and Characterization - Debajani Tripathy; Suresh Sagadevan; Wei Zhang; Santosh K. Tiwari; Srikanta Moharana (Advanced Energy Conversion Materials, 2024)
A solution-casting approach was employed to synthesize polymer composites by incorporating tantalum pentoxide (Ta2O5) and graphene oxide (GO) into a PVDF-HFP (polyvinylidene fluoride-co-hexafluoropropylene) matrix. We conducted a thorough examination of the structure, morphology, and dielectric characteristics of these composites using X-ray diffraction, scanning electron microscopy, and impedance analysis. The current research showed that the composites reinforced with Ta2O5 in the GO-PVDF-HFP material had a consistent and noticeable look inside the PVDF-HFP matrix, suggesting effective integration. Furthermore, the relationship between the dielectric and electrical characteristics of the PVDF-HFP-GO-Ta2O5 composites at different weight percentages of Ta2O5 and frequencies has been investigated. This study revealed that the PVDF-HFP-GO-Ta2O5 composite films exhibited a high dielectric constant of 85, with negligible dielectric loss (< 1.5) and excellent AC conductivity (1 × 10-3) at 102 Hz. This suggests their potential appropriateness for energy storage applications. It may offer a simple and direct way to process PVDF-HFP-GO-Ta2O5 nanocomposite films that have superior dielectric properties. This might enable them to be highly promising candidates for a wide range of energy storage applications.